(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Over the past decade, as traditional and new media and the blogosphere have increasingly engaged with the cult of body beauty, there has been a growing need to further develop philosophical concepts of body culture. Popular interests are not limited to diets and sports lifestyles; rather, the focus was on the virtual body shaped by the mass media. The efforts to "create" a beautiful (and real) body to present on Instagram are contributed by beauty industry professionals who offer a range of services to shape any body; Although virtual bodies are unlimited in their presentation, modern software filters are available to eliminate any shortcomings and highlight each advantage. A real person in this virtual environment often loses their individuality to become an "ideal carrier" of a set of optional body parts, including lips, eyes, noses, etc.; the human body is treated as an investment asset or frame with no inherent characteristics. Key words: physical culture, body culture, philosophy of physical culture, philosophy of physical activity, cult of physical beauty.